2001
DOI: 10.1063/1.1401777
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized carbon nanotips

Abstract: We have developed a carbon nanostructure, which is comprised of high-density carbon nanotips on a graphite layer. These carbon nanotips, with tip diameters of ∼10 nm, are grown by high-density plasma chemical vapor deposition onto Ni-coated Si using an inductively coupled plasma. The Ni on Si changes into NiSi2 by substrate heating. First, a carbon buffer layer and then a graphene sheet are formed on the NiSi2. Then, the carbon nanotips are grown by a C2H2/H2 plasma on the graphene sheet. The carbon nanotips s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Recently, the fabrication of characteristic surfaces for diamond and diamond-like carbon (DLC) has drawn considerable attention due to the excellent physical and chemical properties of these materials [1][2][3][4][5][6][7][8]. With the negative electron affinity, for instance, they have been expected as the most promising field emission materials with a low threshold field to be applied in electron sources, flat panel displays, and a new generation of microwave tubes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the fabrication of characteristic surfaces for diamond and diamond-like carbon (DLC) has drawn considerable attention due to the excellent physical and chemical properties of these materials [1][2][3][4][5][6][7][8]. With the negative electron affinity, for instance, they have been expected as the most promising field emission materials with a low threshold field to be applied in electron sources, flat panel displays, and a new generation of microwave tubes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…With the negative electron affinity, for instance, they have been expected as the most promising field emission materials with a low threshold field to be applied in electron sources, flat panel displays, and a new generation of microwave tubes [9][10][11]. In this case, diamond/DLC films should be prepared with desired surface geometries such as cones or tips with high aspect ratio, which is of vita importance to improve the field-emission properties by introducing the enhancement effect of local field near the tips [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon nanotips have become interesting wing to their low turn-on field for field emission and high emission current. It was reported that they exhibited a turn-on field of 0.1 V mm À1 and a current density of 2 mA cm À2 at a field of 2 V mm À1 , which are of the materials with the lowest turn-on field so far [1]. These data indicate that they are the most promising material for field emission display emitters.…”
Section: Introductionmentioning
confidence: 89%
“…These data indicate that they are the most promising material for field emission display emitters. The carbon nanotips have been successfully synthesized by plasma-enhanced chemical vapor deposition (CVD) on silicon and copper substrates with or without catalysts and the growth mechanism has widely been researched [1][2][3][4]. However, the mechanism has not been well understood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the formation of Ni grains during the pretreatment process plays a key role in growing CNTs; when Ni forms alloys such as NiFe, NiCr, etc. (with SUS substrates) or NiSi 2 (with Si substrates), other isomers of carbon such as carbon nanotips are formed instead of CNT [13], and therefore TiN buffer layers with excellent electrical conductivity (resistivity $25 mV cm) and high melting point ($3200 8C) [9] are usually added to prevent the reaction between catalyst layers and substrates [14]. To create uniform Ni particles, NH 3 gas was introduced for 6 min.…”
Section: Methodsmentioning
confidence: 99%